Implementasi Protokol UPnP pada Perangkat Smart Home Berbasis ESP8266 - Imam Syafi'i Al Ghozaly; Sabriansyah Rizqika Akbar; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Before smart home devices can be used by users, their services and capabilities need to be discovered first. However, there are some issues regarding standardization in that process. Standardization is critical to ensure devices' interoperability. This research proposes Universal Plug and Play (UPnP) protocol as the standard to discover and utilize available smart home devices on the network. Devices' services and capabilities can be learned through UPnP discovery and description. Once discovered, smart home devices can be controlled by sending them control messages or regularly monitored by subscribing to event message which will be sent off by smart home devices whenever their state changed. UPnP protocol was implemented on four different ESP8266 microcontrollers, each of which is connected to a PIR motion sensor, magnetic switch door sensor, SCT-013-000 current sensor, or relay module. Users can search, discover and utilize available smart home devices on the network through a control point application runs on Android. Test results showed that the average time for smart home devices to be fully discovered, to respond to a control message, and to send event message are 279.33 ms, 235.79 ms, and 220.49 ms respectively. Another test results showed that the SCT-013-000 current sensor readings' accuracy was 98.48 %.